2000
DOI: 10.1007/bf02439813
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and apoptosis inhibitor soluble fas antigen in the serum of patients with osteosarcoma and neuroectodermal bone tumors

Abstract: Serum contents of leptin and soluble Fas antigen were measured in 28 patients with osteosarcoma, 7 with neuroectodermal bone tumors, and 17 healthy subjects. The incidence and levels of soluble Fas antigen in patients with osteosarcoma and neuroectodermal bone tumors were higher than in healthy subjects and did not depend on sex and age in both healthy subjects and patients. Serum concentration of leptin in women was higher than in men (both in healthy controls and patients) and was lower in healthy subjects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Acquired resistance protects osteosarcoma tumor cells against apoptosis induced by radiotherapy, chemotherapy and combined therapy in the treatment of tumors (36,37). Reducing the apoptotic resistance of cancer cells and tumors tissues will contribute to the clinical treatment for of with osteosarcoma who have undergone oncotherapy and other comprehensive treatments (38,39). In this study, the data indicated that miR-124 transfection promoted apoptosis of osteosarcoma cells, potentially via regulation of P53, Bcl-2, Apaf-1 and Bad expression.…”
Section: Discussionmentioning
confidence: 69%
“…Acquired resistance protects osteosarcoma tumor cells against apoptosis induced by radiotherapy, chemotherapy and combined therapy in the treatment of tumors (36,37). Reducing the apoptotic resistance of cancer cells and tumors tissues will contribute to the clinical treatment for of with osteosarcoma who have undergone oncotherapy and other comprehensive treatments (38,39). In this study, the data indicated that miR-124 transfection promoted apoptosis of osteosarcoma cells, potentially via regulation of P53, Bcl-2, Apaf-1 and Bad expression.…”
Section: Discussionmentioning
confidence: 69%
“…Resistance to apoptosis is the greatest obstacle to the treatment of human cancer ( 32 , 33 ). Decreasing the apoptosis-resistance of cancer cells and tumors tissues may improve the clinical treatment outcomes of patients with osteosarcoma who have undergone oncotherapy and other comprehensive treatments ( 34 , 35 ). In recent years, TRIM-14 was identified as an oncogene that promotes tumor growth, aggressiveness and tumor angiogenesis; however, knockdown of TRIM-14 expression can significantly inhibit tumor growth, migration, invasion and tumor angiogenesis in human colorectal cancer cells ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immune surveillance of OS may be modulated in situ by the neural and the endocrine systems. Indeed, leptin, which is elevated in subjects with OS (Kushlinskii et al, 2000), plays a significant role in regulating circadian neuroendocrine (e.g., cortisol) and cytokine (e.g., IL-6, IFN) production (Prolo et al, 1998). Taken together, these avenues of basic research suggest novel interventions for patients with mandibular and maxillary OS, or with OS outside of the confines of the head and neck region.…”
Section: Discussionmentioning
confidence: 99%